The role of work-family psychological contract in the relationships between affectivity and job satisfaction - Mat Jusoh, Mardhiah; Ahmad, Aminah; Omar, Zoharah (Canadian Center of Science and Education, 2014)
In recent years, studies have shown that with the increase in the number of dual-career couples and greater job demand from employers, employees have to deal with work-family role imbalance. Hence, many employees have demanded assistance for non-work or family activities. The absence of a strong legal contract on work-family benefits to help employees deal with work-family role imbalance has resulted in employees relying on psychological agreements or contracts. This paper presents a model that includes personality factors (positive affectivity and negative affectivity) as independent variables, work-family psychological contract as a mediator and job satisfaction as the dependent variable. This model was developed based on the ‘conservation of resources theory’ as well as previous research findings. This model extends the content of psychological contract to include work-family issues by introducing the work-family psychological contract concept and postulates the role of work-family psychological contract as a mediator in the relationships between affectivity and job satisfaction.